Implementasi kurikulum merdeka dan dampaknya terhadap prestasi belajar efektif di sekolah dasar - Khadafi, Hafidh Khadafi (Maliki Interdisciplinary Journal, 2024)
The study of the implementation of the Merdeka Curriculum in Elementary Schools shows that there is readiness and positive commitment among teachers in adapting to changes in learning approaches. Through interview analysis, it appears that the teacher understands the concept. Recognizing parental support as important, this research emphasizes the need to increase their understanding to positively influence the achievement of curriculum goals. Significant obstacles arise due to differences with the previous curriculum, especially in the assessment of project-based learning, which requires deeper understanding and additional training. Analysis of assessment aspects shows the effectiveness of implementing formative and authentic assessments by teachers. However, challenges related to teachers’ and parents’ lack of understanding of the Independent Curriculum, especially Independent Learning, can have an impact on achieving curriculum goals. Therefore, joint efforts are needed to increase parental understanding and support, as well as additional training for teachers regarding assessment in the context of the Independent Curriculum. The curriculum encourages teachers to design more interesting and interactive learning experiences, giving students freedom to choose subjects and opening up opportunities to explore talents and potential in various fields.